ESTUDO NO SETOR VAREJISTA: UMA AVALIAÇÃO DOS VENDEDORES E GESTORES - Zamberlan, Luciano; Sparemberger, Ariosto; Büttenbender, Pedro L.; Wagner, Adriano; Becker, Joice T.; Graef, Nelinho D. (Salão do Conhecimento, 2013)
Resumo